2024
DOI: 10.5132/eec.2015.01.10
|View full text |Cite
|
Sign up to set email alerts
|

The use of epibenthic copepod Tisbe biminiensis nauplii to assess the toxicity of seawater samples in Suape Bay (state of Pernambuco; Brazil)

Abstract: Bioassays to determine the toxicity of water have been used worldwide as a tool of environmental monitoring. In the present study, the epibenthic copepod Tisbe biminiensis nauplius is proposed as a test organism for samples of seawater. Survival and the percentage of development from nauplius to copepodite were compared to the embryo-larval development of the sea urchin L. variegatus exposed to the same samples from the Suape estuarine system (state of Pernambuco, Brazil) collected in 2009. T. biminiensis naup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, when exposed to very high CO 2 levels, 388 crustacean larvae as well as for ecotoxicological bioassays (e.g. Williams and Jones, 1999;Souza-Santos et al, 2006;Souza-Santos et al, 2015). However, despite the 416 absence of significant effects on Tisbe sp density at pH 7.7 and 7.3, it is possible -if not 417 likely -that sub-lethal impacts could occur (Fitzer et al, 2012).…”
mentioning
confidence: 99%
“…However, when exposed to very high CO 2 levels, 388 crustacean larvae as well as for ecotoxicological bioassays (e.g. Williams and Jones, 1999;Souza-Santos et al, 2006;Souza-Santos et al, 2015). However, despite the 416 absence of significant effects on Tisbe sp density at pH 7.7 and 7.3, it is possible -if not 417 likely -that sub-lethal impacts could occur (Fitzer et al, 2012).…”
mentioning
confidence: 99%
“…In an area of the Jundiaí River, approximately 30 km upstream of the current study area, where a textile industry is located, Gurgel et al (2016) reported a mortality rate of M. juniae six times higher than the control group, and a reproductive rate 53% lower than that observed in the control group, suggesting the potential ecological impact on ecosystem biota. Other work reported more than 50% reduced survival of M. juniae in surface water samples from estuaries in northeastern Brazil (Nilin et al, 2019) and chronic toxicity in L. variegatus associated with the discharge of domestic and industrial effluents (Souza-Santos & Araújo, 2013).…”
Section: Ecotoxicological Characterizationmentioning
confidence: 97%